2014
DOI: 10.17219/acem/37022
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Mechanical Ventilation in Pediatric Patients in Serbia

Abstract: Background. Mechanical ventilation is a frequently applied therapy in critically ill children and can be lifesaving in many cases. Clinical use of this technique has well documented benefits, but can be associated with different complications and adverse physiologic effects. Objectives. The aim of this study was to investigate the complications and clinical outcome of mechanical ventilation in Serbian pediatric patients. Material and Methods. The study encompassed 42 children with respiratory insufficiency tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Ventilator associated pneumonia, multiple organ failure, septic shock, cardiovascular insufficiency and gastrointestinal bleeding occurs frequently following MV. The frequency of these complications is lower among children under low volume and pressure settings (6) . Increased in severity of the underlying diseases requiring MV is associated with higher rate of these complications.…”
Section: Discussionmentioning
confidence: 98%
“…Ventilator associated pneumonia, multiple organ failure, septic shock, cardiovascular insufficiency and gastrointestinal bleeding occurs frequently following MV. The frequency of these complications is lower among children under low volume and pressure settings (6) . Increased in severity of the underlying diseases requiring MV is associated with higher rate of these complications.…”
Section: Discussionmentioning
confidence: 98%
“…Also, majority of children were below 1 yr. of age (59.2%) and had weight below 5 kg (48%). Studies done by Tanil Kendril et al, [12] Beenish Mukhtar [13] and Snezana Rsovac et al [14] also found high incidence in male children.…”
Section: Discussionmentioning
confidence: 98%
“…Respiratory failure was the most common indication for MV in many studies. [14,15,16] Farias et al [17] in the study published in 2004 observed acute respiratory failure as the cause for initiation of invasive ventilation in 72% of the cases, whereas it was 64.8% in the study by Tanil Kendril et al [12] and 59.18% in a study from Brazil. [18] Acute pulmonary disease has been reported as the main reason for the initiation of MV in developing countries, whereas postoperative state seems to be the main indication for ventilatory support in developed countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations